Guest editorial theories and methods for advanced wireless relays - Issue I - Hua, Y.; Bliss, D.; Gazor, S.; Rong, Yue; Sung, Y. (2012)
The 46 papers focusing on the theme of "Theories and Methods for Advanced Wireless Relays" have been divided into two groups to be published in two separate issues. This first issue includes 23 papers on relay performance bound, MIMO relay beamforming, relay channel estimation, two-way and shared relays, full-duplex relays, and security for relay networks. The second issue includes papers on coding for relay networks, medium access control for relays, implementation ans system performance studies.